Pengaruh Penggunaan Media Blooket terhadap Hasil Belajar Siswa Kelas III pada Materi Jenis-Jenis Pekerjaan Mata Pelajaran IPS - Dwi Ayu Lestari; Rury Rizhardi; Ida Suryani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to determine the effect of using Blooket media on the learning outcomes of third-grade students on the subject of types of work in Social Sciences (IPS) at SDN 06 Rambang Kuang. This study uses a quantitative approach with experimental research in the form of quasi-experiments and Pretest-Posttest Control Group Design. The subjects of the study were third-grade students, with class III A consisting of 19 students as the control class and class III B consisting of 16 students as the experimental class. The instrument used was a multiple-choice test of 10 questions to measure learning outcomes before and after treatment. The experimental class was given learning using Blooket media, while the control class used conventional methods. Based on the results of statistical tests showing a t-count value of 1.749 < t-table 2.035 and a sig. 2-tailed value of 0.090 > 0.05. Thus, it can be concluded that there is no effect of using Blooket media on the learning outcomes of third-grade students on the subject of types of work in Social Sciences.